Peran Perbankan Syariah terhadap Eksistensi UMKM Industri Rumah Tangga Batik - Hana Zunia Rini (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This study aims to determine the degree level of Islamic banking participation to support the financial inclusion for the Micro Small and Medium Enterprises (SME). Through the qualitative descriptive approach, with batik Laweyan as its case study, the result revealed that the role of Islamic banking in the existence of SME batik Laweyan still very low, the socialization of their product also minimum, thereby the SME batik Laweyan not interested in doing loan or financing. Some of the influencing factors are Islamic banking considered having complicated in the procedure, unfamiliar term used for their product, feeling uncertain and afraid to make sharia the bank financing.Keywords:Islamic banking, SME, Batik Laweyan